Chronic Illness in Adolescents - Yadav, Ritu; K, Kavitha (Journal of Neonatal Surgery, 2025)
New generation chronic illness consumers prove to be a major concern for public health systems, especially in L&M INs including India. As indicated by the write up, this paper looks at the prevalence, impact, and the recurrence of steady circumstances inclusive of respiratory issues like asthma, diabetes, and prevalent emotional well-being challenge modulo young Indian people. Such issues are aggravated by aspects that include fast urbanization, changing living standards, and financial pressures which lead to a range of physical, psychological, and social challenges. The review also stresses the need for integrated health care systems, prevention and on-going health care reforms, early interventions, and programs at home and in the global setting for the well-being of adolescents. The following issues have to be addressed to decrease the negative impact of chronic illness and enhance adolescents’ future in India